2012
DOI: 10.1017/s0007114511007033
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine-lowering therapy does not lead to reduction in cardiovascular outcomes in chronic kidney disease patients: a meta-analysis of randomised, controlled trials

Abstract: The efficacy of homocysteine (Hcy)-lowering therapy in reducing the risk of CVD among patients with chronic kidney disease (CKD) remains controversial. We performed a meta-analysis to determine whether pooling the data from the few small randomised, controlled trials that address this topic would improve the statistical power of the analysis and resolve some of the inconsistencies in the results. Randomised, controlled clinical trials (RCT) were identified from MEDLINE, EMBASE, www.clinicaltrials.gov, the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 39 publications
(84 reference statements)
1
19
0
Order By: Relevance
“…A meta-analysis of 10 studies concluded that Hcy-lowering therapy is not associated with a significant decrease in the risks for CVD events, stroke, and all-cause mortality among patients with CKD [58]. The deviation from the previous meta-analysis may reflect the enrollment in some RCTs of a high number of DM participants and their performance in grain fortification areas.…”
Section: Folate and Vitamin B: Interventional Studies On Cvd In Ckd Pmentioning
confidence: 99%
“…A meta-analysis of 10 studies concluded that Hcy-lowering therapy is not associated with a significant decrease in the risks for CVD events, stroke, and all-cause mortality among patients with CKD [58]. The deviation from the previous meta-analysis may reflect the enrollment in some RCTs of a high number of DM participants and their performance in grain fortification areas.…”
Section: Folate and Vitamin B: Interventional Studies On Cvd In Ckd Pmentioning
confidence: 99%
“…Almost 40% of this mortality is attributable to cardiovascular (CV) disease [2]. Unfortunately, there seems to be little hope in sight for improvements since almost all large, randomized controlled trials have persistently shown no survival benefit from several “new” treatment approaches: use of statins [3], ESA's [4], vitamin D or cinacalcet [5,6], antioxidant or homocysteine lowering therapies [7], prolonged or more frequent dialysis sessions [8] or convective therapies [9]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that Hcy could block the Cys transport at the level of the ASC transporter [21]. Sekhar and co-workers [22] showed indeed that Cys levels are diminished in T2D erythrocytes, most probably because of the block of the transporter. In addition, we found high levels of tHcy also in T2D patients at stage 0 of CKD.…”
mentioning
confidence: 98%
“…However, clinical studies have shown that folic acid therapy is not very effective in normalizing hyperhomocysteinemia in uremic patients [4]. In a meta-analysis of randomized controlled trials, Pan and collaborators [22] reported that the estimated relative risk of CVD was not significantly different for cardiovascular events regardless of dialysis or in combination with B-vitamin therapy or the degree of reduction of Hcy levels, supporting the conclusion that Hcy-lowering therapy was not associated with a significant decrease in the risk for CVD events, stroke and all-cause mortality among patients with CKD.…”
mentioning
confidence: 99%